Implementation Of Peer Teaching Learning Methods In Honoring Arabic Speaking Skills In Islamic Education Institutions - Nafisatul Faudah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
The purpose of this study is to describe the implementation of peer teaching learning methods in honing Arabic speaking skills in Islamic educational institutions. The research method in this study uses a qualitative approach and the type of research is library research. The results of the research show that (1) speaking skills are the ability to express articulation sounds or words to express thoughts in the form of ideas, opinions, desires, or feelings to the interlocutor (2) the peer teaching method or what is often called peer tutoring is a method of peer teaching. which focuses on learning activities for students. Students are given the opportunity to share their knowledge and skills with other students. In addition to being smart, tutors must have a high sense of sociality and be accepted by other students. (3) the implementation of peer teaching learning in honing Arabic speaking skills is carried out based on the preparation, implementation and evaluation stages. From this explanation, the peer teaching method that has been offered is expected to be a solution to various problems in learning Arabic speaking skills.